Patterns of managerial action: an empirical analysis of German sport managers. (2nd December 2011) - Kaiser, Sebastian; Schütte, Norbert
Based on the assumption that the organisational society is divided into three clearly defined economic sectors, it seems an obvious assumption to adequately differentiate the educational curriculum according to these three sectors. By examining the characteristics of the different tasks of sport managers within the abovementioned sectors, it can be noted that it is possible to speak of a general job profile, although significant individual interior deviations are evident. With the use of cluster analysis techniques, empirical manager types can be identified, which cannot easily be matched into the theoretical sector typologies.